KORELASI FAKTOR DEMOGRAFI, NUTRISI DAN ANTROPOMETRI TERHADAP KEJADIAN HIPERTENSI PADA PETUGAS KEAMANAN DI UNIVERSITAS TARUMANAGARA JAKARTA - Santoso, Alexander Halim; Lontoh, Susy Olivia; Gunaidi, Farell Christian; Istikanto, Ferdian Harum; Destra, Edwin; Kurniawan, Junius; Anggraeni, Natasha; Cahyadi, Stanley Surya; Mayvians, Tizander (Ebers Papyrus, 2021)
Introduction Hypertension is a silent killer and causes various complications and even death. According to World Health Organization (WHO), hypertension causes 9.4 million deaths per year worldwide. Hypertension is more common in countries with low to middle economic status than in high-income countries. Based on the results of the Riskesdas 2018, there was an increase in the prevalence of hypertension in people aged ?18 years, from 23.8% to 34.1%. DKI Jakarta Province is one of the provinces with a high prevalence of hypertension (34%). University security officers are a group of workers who are at risk of hypertension. This may be due to the work style of the University security officers who are mostly standing and sitting. Studies of security personnel are still rare. Methodology This study is an analytical study with a cross-sectional design to see the correlation of demographic, nutritional and anthropometric factors on hypertension. Results In this study, a total of 90 male  subjects were recruited, with an average age of 30.09 years, 84.4% were educated to high school level, 80% smoked, 88.9% consumed coffee, 92,2% exercised regularly. In this study, it was found that the subject's average body weight was 70.56 kg, the average body mass index of the subject was 24.79 kg/m2, 32.2% of the subjects had an waist circumference of more than 90 cm and the average hip circumference was 97.24 cm. In this study, it was found that 48.9% had high blood pressure, where 8.9% of subjects had systolic blood pressure of 140 mmHg and 47.8% of subjects had diastolic blood pressure of ³90 mmHg. There was a positive and significant correlation between age, body weight, BMI, waist circumference and hip circumference with hypertension (p<0.05). Conclusion Increasing age, weight, body mass index, abdominal circumference and pelvic circumference were correlated with hypertension in security officers